Herbal Medicines: The Double-Edged Sword for Brain—A Narrative Update - Khandelwal, Ankur; Niranjana, S.; Sarma, Kalyan; Hussain, Masaraf; Dikshit, Priyadarshi; Singh, Gyaninder P. (Journal of Neuroanaesthesiology and Critical Care, 2025)
Phytochemicals or herbal medicines (HMs) with neuroprotective and nootropic properties are being increasingly utilized in various neurological conditions owing to their antioxidative, anti-inflammatory, and antiapoptotic properties, as well as their role in immune regulation, hormonal regulation, and modulation of neurotransmitters and ion channels. While HMs are often regarded as safe, they are not without risks. The aim of this review was to know the various neurological and non-neurological side effects of long-term consumption of neuroprotective and nootropic phytochemicals. An electronic search was conducted using the following databases from January 2000 to December 2023: PubMed, PubMed Central, Embase, Scopus, and Science Citation Index (Web of Science). Only studies published in the English language were considered. The search used key terms such as “Herbs,” “Phytochemicals,” “India,” “Asia,” “Neuroprotection,” “Neurological diseases,” and “Complications.” The sources included research articles, systematic reviews and meta-analyses, narrative reviews, and editorials. Letters to the editor, commentaries, abstracts only, and unpublished data were excluded. While HMs are increasingly being used therapeutically for various neurological and non-neurological conditions, they also carry the risk of adverse effects due to contamination, adulteration, direct effects of metabolites, herb–drug interactions, interindividual susceptibility, and other factors. In addition, widespread availability, over-the-counter sale, and unsupervised dosing are the key reasons for their unregulated prolonged use. As such, correct identification of HMs and consequent assessment of their toxicological profile are deemed extremely crucial. Neurotoxicity testing for HMs is challenging considering the limitations of traditional methods (morphological, microscopic, and chemical); nevertheless, in the recent years, several novel procedures have been developed. Large studies are warranted to establish the safety profile of consuming HMs either alone or in combination in humans.
Keywords: herbs; neuroprotection; phytochemicals; safety; toxicity